(untitled) (Journal of Pathology of Nepal, 2016)
Glucose-6-phosphate dehydrogenase deficiency is the most common enzymatic defect of red blood cells, which increases the vulnerability of erythrocytes to oxidative stress leading to hemolytic anemia. Since its identification more than 60 years ago, much has been done with respect to its clinical diagnosis, laboratory diagnosis and treatment. Association of G6PD is not just limited to anti malarial drugs, but a vast number of other diseases. In this article, we aimed to review the history of Glucose-6-phosphate dehydrogenase, the diagnostic methods available along with its association with other noncommunicable diseases.